Potential Effect of Medicinal Plants on the Prevention of Gastric Ulcer: Mechanism of Actions - Qader, Suhailah Wasman; Chua, Lee Suan; Fournier, Janelle; Ozdemir, Mehmet (Journal of Pharmacy and Nutrition Sciences, 2022)
Medicinal plants have been widely studied to identify plant-based anti-gastric ulcer medicines. The mechanism of gastroprotective action is important to discover the potential lead compounds for drug development. All relevant articles between 2011 and 2021 focusing on Malaysian plants were collected and analyzed to understand the underlying pathways. Keywords include peptic ulcer, gastric ulcer, NSAIDs (Non-Steroidal Anti-Inflammatory Drugs), Helicobacterpylori, medicinal plant, gastroprotection, antiulcer, acid secretion, cytoprotective, and digestion processes were applied in the search engines. Twenty-two of the plants had been reported based on the collected data. The review concludes that Malaysian plants could protect the gastric wall against necrotizing agents like ethanol and NSAIDs. This is mainly due to four critical defensive mechanisms: cytoprotective barriers, regulation of heat-shock protein 70 (HSP70) and pro-apoptotic protein (BAX), gastric acid secretion, and antioxidant capability. The mechanisms have been illustrated in the schematic diagrams for better understanding.